Study of the Pattern and Frequency of Road Traffic Injuries in Car Occupants in the Eastern Part of Iran - Soroosh, Davood; Nematshahi, Mohammad; Javadinia, Seyed Alireza; Hesamifard, Mitra (International Journal of Medical Toxicology and Forensic Medicine, 2020)
Background: Since Iran has one of the highest mortality rates of car accidents in the world, the study of the pattern and reasons of trauma in car occupants can provide useful information to determine the underlying causes of injuries and deaths in traffic accidents. Accordingly, this study was conducted to determine the pattern, frequency, and causes of traumatic injuries caused by traffic accidents in car occupants. Methods: This cross-sectional study was conducted during the first 6 months of 2017 in Shahid Beheshti Hospital in Sabzevar City, Razavi Khorasan Province, Iran. The data were obtained from the medical records of patients and the checklist designed by our research team. Results: During the period of study, 300 people were involved in car accidents, of whom 58.3% were men with an average age of 35.16 years. In both sexes, 29.3% of the subjects were in the age group of 30-40 years. Twenty-two car occupants were involved in non-injury car accidents. No significant relationship was found between traumatic injuries and variables of sex, seatbelt use, airbag deployment, and the seat occupant in the cars (P>0.05), as well as between death and variables of sex, airbag deployment and seat occupant in cars (P>0.05). But there was a significant relationship between death and fastening seat belts (P=0.003). Conclusion: The results of this study revealed that sex, airbag deployment, and seat occupant had no effect on traumatic injury or mortality rate in the car occupants. However, fastening the seatbelt can reduce the mortality rate in car occupants, but it does not impact the traumatic injuries rate.